Robust Analysis of Multimodal Biometric Verification System Under Various Spatial Noise Conditions - Gowda, Supreetha HD; Kumar, G Hemantha; Imran, Mohammad (International Journal of Computer Sciences and Engineering, 2025)
Instinctive person verification system still faces various challenges in desirable performance due to dependent and independent noise. Most of the physiological biometric modalities are 2-D images, which may have high probability to get affected from noise. This work proposes a comprehensive analysis of robustness of various unimodal and multimodal biometric systems in clean and noisy conditions. On each stage of biometric system we emphasize, feature extraction, level of fusion and suitable normalization schemes. For feature extraction, methods we have employed subspace, kernel and texture based methods and we have subjected the data on all four levels of fusion schemes- sensor, feature, match score and decision level. The objective of this paper is to analyze the robustness of unimodal systems with distinct modalities and evaluate the robustness of a multimodal system with combinations of two, three and four modalities at different levels. All the experiments were evaluated for both clean and noisy data with virtually generated noises of Gaussian and Salt & Pepper methods, and were applied on all biometrics modalities considered for experimentation. The synthetic multimodal database was prepared from standard database of Face, Palmprint, Finger knuckleprint and Handvein. The obtained results and observations in terms of GAR (Genuine Acceptance Rate) show that palmprint with LPQ features are most effective in unimodal systems. In case of multimodal systems, combination of Face (KICA) and Palmprint (LPQ) are most beneficial. This work also suggests some important guidelines on selection of suitable biometric modality, feature extraction algorithms and fusion scheme